Reconstitution of immune cell interactions in free-standing membranes - Jenkins, E; Santos, AMDC; O'Brien-Ball, C; Felce, JH; Wilcock, MJ; Hatherley, D; Dustin, ML; Davis, SJ; Eggeling, C; Sezgin, E (Company of Biologists, 2018)
The spatiotemporal regulation of signalling proteins at the contacts formed between immune cells and their targets determines how and when immune responses begin and end. Therapeutic control of immune responses will therefore rely on thorough elucidation of the molecular processes occurring at these interfaces. However, the detailed investigation of each component's contribution to the formation and regulation of the contact is hampered by the complexities of cell composition and architecture. Moreover, the transient nature of these interactions creates additional challenges, especially for using advanced imaging technology. One approach to circumventing these problems is to establish in vitro systems that faithfully mimic immune cell interactions, but allow complexity to be 'dialled-in' as needed. Here, we present an in vitro system making use of synthetic vesicles that mimic important aspects of immune cell surfaces. Using this system we begin to explore the spatial distribution of signalling molecules (receptors, kinases and phosphatases) and how this changes during the initiation of signalling. The GUV/cell system presented here is expected to be widely applicable.